High-Intensity Interval Training (HIIT): Impacts on Cardiovascular Fitness and Muscle Development - Guifang Liu; Haoyuan Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The aim of research study is determining that high intensity interval training related to impact on cardiovascular fitness also that muscle development. High-Intensity Interval Training (HIIT) has emerged as a game-changing method to fitness, upending old notions of exercise. This dynamic training style, which consists of alternating bursts of strong work and brief recuperation periods, is unrivalled in terms of efficiency and efficacy. The ramifications of HIIT range from cardiovascular health and muscular growth to time-efficient workouts for people who lead hectic lives. HIIT has been shown to be a powerful accelerator for cardiovascular fitness, increasing aerobic capacity, enhancing heart function, and affecting important metabolic indicators. Simultaneously, its involvement in muscular growth defies traditional wisdom, activating fast-twitch muscle fibres and inducing a hormonal response that promotes strength and endurance. For determine the research study used SPSS software and generate results included descriptive statistic, correlation coefficient, the model summary also that regression analysis between them. HIIT's adaptability is reflected in its applications, which include general fitness, weight management, and sports performance. Its flexibility to varied contexts, along with the minimum time investment necessary, makes it a viable alternative for a wide range of people. As a result, HIIT has public health implications, addressing inactive lifestyles and providing a realistic answer to time restrictions. While embracing HIIT's revolutionary potential, care is advised. To reduce the danger of overtraining and injury, mindful integration, effective education, and individualized methods are essential. The overall result shows direct and significant impact of cardiovascular fitness and muscle development related to the high intensity interval training. As HIIT continues to transform fitness landscapes and influence industry practices, its impact on individuals' overall well-being remains significant, establishing it as more than a trend but a cornerstone in the unfolding story of exercise and health.